PENGARUH MOTIVASI DAN KOMPETENSI TERHADAP KEPUASAN KERJA DAN DAMPAKNYA PADA KINERJA KARYAWAN POLITEKNIK LP3I BANDUNG - D Purnomo (POLITEKNIK LP3I JAKARTA, 2016)
Achievement of the employee's performance will usually be preceded by a prior job satisfaction, is not uncommon satisfaction resulting from the spirit of the work as a source of motivation combined with the competence of employees who bersangkutan.Penelitian is intended to identify and assess the motivation and competencies possessed by the employee, the amount of influence both these variables to work satisfaction and job satisfaction impact on the performance of employees indicated.There needs to be a fourth measurement variables in this study at the Polytechnic LP3I Bandung, the postscript was established to eradicate the existence of unemployment in Indonesia. Measurement as outlined in this study, conducted by the method deskriprif verification with proportional cluster sampling technique of random sampling.Based on the study, showed that there is influence of motivation terhdadap job satisfaction for 78,8%, there is the influence of competence terhdadap job satisfaction for 20,8%, job satisfaction affect the performance of 84,4%Keyword : MOTIVATION, COMPETENT, WORK SATISFACTION